Texts From Iraqi Museum - Hammoodi, Hasan M. (Al-Adab Journal, 2021)
The paper presents the research a study of five texts from the Iraqi Museum (confiscation) and included the verb "receive" (šu-ba-ti/ maḫāru). On the other hand, represents a less intensive form of take, more along the lines of receive, get, accept, and one that depends on context, on how the speaker or writer perceives the event. This texts it back to Ur III Dynasty (2112- 2004 BC), and dated during kings dAmar- dSu'en, dŠu- Su'en, and dIbbi- Su'en. These texts contained different materials: lard, brick salt, medicinal plant, spice, a type of groats, and barley.